Code Switching and Code Mixing in English Language Learning during Online Learning in Covid-19 Outbreak - Pratama, Putu Arya (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
In learning English, language mixing is used more often than just monotonically using their mother tongue. A code is a kind of system used in communication between people. Both code mixing and code switching are oftentimes used by society while speaking in two or more languages, especially in the educational field. Therefore this study concern the use of code-switching in language learning. In determining the result of the study, the qualitative method is applied. The subject of the study is eleventh-grade students it is possible in finding code-switching in the form of daily dialogue and learning process. The techniques of data collection used observation. The result of the data analysis shows that code-switching is commonly done during the teaching and learning process, particularly for this online learning period which is impacted by the Covid-19 outbreak. This code-switching is necessary to conduct in avoiding misunderstandings in dialogue, increase the level of material comprehension, maximize classroom interaction, and create a good relationship between student and teacher.